DAMPAK DIGITAL DIVIDE TERHADAP AKSESIBILITAS LAYANAN E-COURT BAGI MASYARAKAT PEDESAAN DALAM PENYELESAIAN SENGKETA PERDATA - Fadhiilah Ayu Ramadhani; Listi Oktavia Safitri; Sri Handayani (CV. Denasya Smart Publisher, 2026)
Advances in information technology have prompted the Supreme Court of the Republic of Indonesia to implement an electronic court system (e‑Court) as part of judicial bureaucratic reform to realize the principles of simple, fast, and low‑cost justice. However, the implementation of e‑Court faces the reality of a digital divide, particularly in rural areas, which is characterized by limited network infrastructure, low device ownership, and inadequate levels of digital and legal literacy. This study aims to analyze the impact of the digital divide on the accessibility of e‑Court services for rural communities in the settlement of civil disputes, as well as to formulate affirmative and inclusive policy recommendations. This qualitative research uses a normative and descriptive-analytical juridical approach based on a literature review of relevant laws, regulations, court decisions, and previous scholarly works. The findings indicate that, without systematic policy intervention, judicial digitalization has the potential to create technological elitism that further marginalizes rural communities. Therefore, the state needs to strengthen ICT infrastructure, implement legal digital literacy programs, and provide inclusive e‑Court services for rural communities in order to ensure the realization of justice.